Legal Protection for Victims of Sexual Violence in Higher Education from a Victimology Perspective - Nabella Dellia Putri; Agus Mulyawan; Nuraliah Ali (Journal of Law, Politic and Humanities, 2025)
Sexual violence is a serious issue in higher education institutions. To address and combat sexual violence in universities, several regulations have been enacted, including Ministry of Education, Culture, Research, and Technology Regulation No. 30 of 2021 on the Prevention and Handling of Sexual Violence in Higher Education, which was later replaced by Regulation No. 55 of 2024, along with the Law on Sexual Violence Crimes. This paper aims to examine the legal protection for victims of sexual violence in universities and explore the application of a victimological perspective for further understanding. The research employs a juridical-normative methodology, utilizing primary and secondary legal sources, as well as non-legal materials. The findings indicate that the regulation of victim protection in higher education is adequately addressed in Ministry of Education Regulation No. 55 of 2024. However, efforts to enhance victim protection could be further strengthened by adopting a victim-centered approach, victim-centered justice, and other victimology-based solutions.